Electronic Voting: 9th International Joint Conference, E-Vote-ID 2024, Tarragona, Spain, October 2–4, 2024, Proceedings - Duenas-Cid, David; Roenne, Peter; Volkamer, Melanie; Budurushi, Jurlind; Blom, Michelle; Rodríguez-Pérez, Adrià; Spycher-Krivonosova, Iuliia; Castellà Roca, Jordi; Barrat Esteve, Jordi (Lecture Notes in Computer Science, 2025)
This open access book constitutes the proceedings of the 9th International Joint Conference on Electronic Voting, E-Vote-ID 2024, held in Tarragona, Spain, during October 2-4, 2024. The 10 full papers included in this book were carefully reviewed and selected from 36 submissions. They present research on all aspects of the mechanization of reasoning with tableaux and related methods. The papers cover a wide range of topics connected with electronic voting, including experiences and revisions of the actual uses of E-voting systems and corresponding processes in elections.